Transforming Malaysia Towards an Innovation-Led Economy By Leveraging on Innovative Human Capital - Hasliza Abdul Halim; Noor Hazlina Ahmad (Bina Nusantara University, 2012)
Fostering “pioneering minds” is extremely important especially in the effort to shift Malaysia towards an innovation-led economy. The Malaysian government is confident of achieving this transformation agenda provided that the human capital is leveraged in ensuring innovation at the highest level. The primary aim of this research is to investigate the predictors that could nurture the “pioneering minds” by exploring the innovative performance of human capital from the perspective of social embedment and pro-innovativeness organisational architecture which could subsequently lead to excellent organisational performance. This research contributes to the existing literature on human capital and innovation by having better understanding on the specific factors that nurture the “pioneering minds” which are crucial for innovative performance.